2019
DOI: 10.17576/jsm-2019-4809-01
|View full text |Cite
|
Sign up to set email alerts
|

Haematological and Biochemical Responses of Juvenile Malabar Blood Snapper (Lutjanus malabaricus Bloch & Schneider, 1801) Exposed to Different Rearing Temperatures and Diets

Abstract: This study is conducted to examine the impacts of different rearing temperature and diet variation on haematological and serum biochemical parameters on the juvenile Lutjanus malabaricus, a commercially important fish species in were divided into eight treatments (4 temperatures × 2 diets) each with three replicates of five juveniles each. Fish were subjected to four different rearing temperatures (22, 26, 30 and 34°C) and fed with a commercial pellet and a natural shrimp diet. After 30 days of experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…Stress causes an increase in oxygen demand in fish, which causes them to compensate with a variety of compensatory actions such as increased breathing frequency [ 35 ] or decreased synthesis of Hb ( Table S2 and see review [ 36 ]). In the present review, the decrease of Hb with many different stressors such as ammonia [ 25 , 37 ], low temperature [ 38 ], microplastics [ 39 ], pollutions [ 40 ], pathogens [ 41 , 42 ], and heavy metals [ 43 ] were observed ( Table S2 ). It seems that this decrease has been a global response to stress given that regardless of kind of stress and species, the Hb was decreased.…”
Section: Haemoglobinmentioning
confidence: 89%
See 1 more Smart Citation
“…Stress causes an increase in oxygen demand in fish, which causes them to compensate with a variety of compensatory actions such as increased breathing frequency [ 35 ] or decreased synthesis of Hb ( Table S2 and see review [ 36 ]). In the present review, the decrease of Hb with many different stressors such as ammonia [ 25 , 37 ], low temperature [ 38 ], microplastics [ 39 ], pollutions [ 40 ], pathogens [ 41 , 42 ], and heavy metals [ 43 ] were observed ( Table S2 ). It seems that this decrease has been a global response to stress given that regardless of kind of stress and species, the Hb was decreased.…”
Section: Haemoglobinmentioning
confidence: 89%
“…Unsurprisingly, the present literature search revealed that stress decreased BP and showed that this parameter can be a reliable indicator of stress ( Table S2 ). Herbicides in snow trout ( Schizothorax plagiostomus ) and common carp [ 72 , 88 , 99 ], low-temperature stress in Malabar blood snapper ( Lutjanus molabaricus ) [ 38 ], microplastics in Nile Tilapia [ 39 ], ammonia in rockfish ( Sebastes schlegelii ) [ 37 ], Aeromonas hydrophila in ningu [ 41 ], reovirus in grass carp ( Ctenopharyngodon idella ) [ 42 ] and fungus toxin in common carp [ 100 ] stimulated the decrease of BP. Furthermore, the mean corpuscular volume (MCV), mean corpuscular haemoglobin (MCH) and MCHC fluctuated between studies showing that they cannot be reliable enough as a biomarker of stress.…”
Section: Blood Performancementioning
confidence: 99%
“…Fish were anaesthetized with clove oil (99% purity, Talya Bitkisel Urunler Ind. Co., Ltd., Antalya, Turkey; 200 mg L −1 ) until ventilator movements stopped in order to lessen handling stress [38]. Fish were rapidly caught, and blood samples were collected from the caudal vein using a heparinized syringe and transferred to tubes that contained the anticoagulant substance EDTA.…”
Section: Surgical Protocol and Haematological Analysismentioning
confidence: 99%
“…Fish were anesthetized with clove oil (99% purity, Talya Bitkisel Urunler Ind. Co. Ltd., Antalya, Turkey; 200 mg L − 1 ) until ventilator movements stopped in order to lessen handling stress (Mazumder et al 2019). Fish were rapidly caught, and blood samples were collected from the caudal vein using a heparinized syringe and transferred to tubes that contained the anticoagulant substance EDTA.…”
Section: Surgical Protocol and Haematological Analysismentioning
confidence: 99%